Integration of Knowledge Management Capability (KMC) mediated by AI Capability and Organizational Learning Agility for Sustainable Competitive Advantage in the Digital Era in Binjai City MSMEs - Firmansyah; Rindi Andika; Iskandar Muda (CERED Indonesia Institute, 2025)
This research seeks to examine the function of HR Analytics as a moderating variable in the integration model of This study aims to examine the influence of Knowledge Management Capability, AI Capability, and Organizational Learning Agility on Sustainable Competitive Advantage in organizations using the Resource-Based View and Dynamic Capability approaches. Analysis was conducted using PLS-SEM to assess the direct and indirect effects between variables. The results show that AI Capability has a significant positive effect on Sustainable Competitive Advantage (36.1%), confirming that the use of AI plays a crucial role in building long-term competitiveness. In addition, Knowledge Management Capability is the most dominant variable, with a very strong influence on AI Capability (85.1%), and has a significant impact on Organizational Learning Agility (22.8%) and Sustainable Competitive Advantage (33.2%). This study also found that Knowledge Management Capability influences Sustainable Competitive Advantage indirectly through AI Capability (30.7%), which is the strongest mediating pathway, and through Organizational Learning Agility (14.3%). These findings confirm that knowledge management is a fundamental element in strengthening technological capabilities and learning agility, which ultimately enhances sustainable competitive advantage. This research provides theoretical contributions to the development of a knowledge-based integration model as well as practical implications for organizations in designing sustainable digital transformation strategies.